1992
DOI: 10.1016/0735-1097(92)90011-b
|View full text |Cite
|
Sign up to set email alerts
|

Improved myocardial ischemic response and enhanced collateral circulation with long repetitive coronary occlusion during angioplasty: A prospective study

Abstract: This study confirms a progressive adaptation of myocardial ischemia to repetitive coronary occlusions and supports the concept that sequential episodes of myocardial ischemia are a stimulating factor for the recruitment of collateral channels in humans. These results also suggest that enhancement of recruitable collateral circulation might be an underlying mechanism of myocardial ischemic preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(87 citation statements)
references
References 24 publications
3
80
1
3
Order By: Relevance
“…Murry et al (39) initially showed that myocardium subjected to brief, repeated episodes of sublethal ischemia becomes highly tolerant to the consequences of subsequent lethal ischemia. This endogenous cellular adaptation, more commonly referred to as ischemic preconditioning (IPC), has been documented in many mammalian species, including humans (40)(41)(42), and is not necessarily exclusive to the heart. IPC-mediated cytoprotection is biphasic: an early phase develops within minutes of the initial ischemic event and lasts 2 h to 3 h (39), while the delayed phase is initiated within 12 h and lasts three to four days (43,44).…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…Murry et al (39) initially showed that myocardium subjected to brief, repeated episodes of sublethal ischemia becomes highly tolerant to the consequences of subsequent lethal ischemia. This endogenous cellular adaptation, more commonly referred to as ischemic preconditioning (IPC), has been documented in many mammalian species, including humans (40)(41)(42), and is not necessarily exclusive to the heart. IPC-mediated cytoprotection is biphasic: an early phase develops within minutes of the initial ischemic event and lasts 2 h to 3 h (39), while the delayed phase is initiated within 12 h and lasts three to four days (43,44).…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…Several clinical studies have observed progressive decreases in chest pain, ST-segment elevation, and lactate production on subsequent compared with first 60-to 90-second intracoronary balloon inflation. 239,240 The potassium channel blocker glibenclamide can prevent the beneficial effects of repeated balloon angioplasty. Adenosine can mimic the protective effect, 241 whereas adenosine antagonists block it, 242,243 findings that parallel experimental observations in the animal laboratory.…”
Section: Clinical Evidence For Preconditioningmentioning
confidence: 99%
“…Adenosine can mimic the protective effect, 241 whereas adenosine antagonists block it, 242,243 findings that parallel experimental observations in the animal laboratory. Some studies that assessed collateral flow showed no evidence of recruitment during sequential balloon inflations, 239 although one study 240 did report that in about half of the patients, there was recruitment.…”
Section: Clinical Evidence For Preconditioningmentioning
confidence: 99%
“…The modification of ischaemia during the second inflation did not appear to be due to an increase in collateral blood flow. In a subsequent angioplasty study undertaken by Cribier et al, chest pain and ST segment changes were also attenuated during the second balloon inflation but in contrast to Deutsch's study, Cribier observed some opening of collateral vessels after the first inflation [60]. In the most recent study of this type, Taggart et al found that the severity of ischaemia (assessed by cardiac electrogram) during the second balloon inflation was reduced and it is thought that this attenuation of ischaemia could be due to the opening of KATP channels during the first balloon inflation [61].…”
Section: Preconditioning Models In Human Myocardium In Situmentioning
confidence: 78%